A year of pandemic for European particle radiotherapy: A survey on behalf of EPTN working group. (May 2022) - Barcellini, Amelia; Massaro, Maurizio; Dal Mas, Francesca; Langendijk, Johannes A.; Høyer, Morten; Calugaru, Valentin; Haustermans, Karin; Timmermann, Beate; Thariat, Juliette; Scartoni, Daniele; Vennarini, Sabina; Georg, Petra; et al.
Highlights: We investigated the effect of Covid-19 pandemic in the treatment practice of particle therapy institutions in Europe. The number of in-person first evaluations and follow-up visits decreased, but telemedicine was implemented. During the pandemic hypofractionation and short-schedule of chemotherapy, when applicable, were preferred. A delay in cancer diagnosis and oncological staging leading to an increment in more advanced diseases at first presentation. Abstract: Objectives: To provide an overview of the impact of the pandemic on the clinical activity and take a snapshot of the contingent challenges that European particle therapy centers are called to face, we surveyed the members of the European Particle Therapy Network (EPTN). Material and methods: A 52-question survey was conducted from 4th April 2021 to 30th July 2021 using the Google Forms platform. Three dedicated sections analysed the clinical context of each participating institution, the staff management, and the clinical changes in the oncological workflow. Results: Out of the 23 contacted European hubs of particle radiotherapy, a total of 9 (39%) responded to the survey. The number of in-person first evaluations and follow-up visits decreased, but telemedicine was implemented. Multidisciplinary tumour board discussions continued during the outbreak using web-based solutions. A delay in cancer diagnosis and oncological staging leading to an increment in more advanced diseases at first presentation was generally observed. Even if the total number of treatments (photons and particles) in the responding institutions showed a trend of decrease, there was or a stable situation or slight increase in particle treatments. The clinical treatment choices followed the national and international scientific recommendations and were patient/disease-oriented. Hypofractionation and short-schedule of chemotherapy, when applicable, were preferred. Conclusions: Our findings show a rapid and effective reaction of European particle RT hubs to manage the healthcare crisis. Considering the new waves and virus variants, the vaccination campaign will hopefully reduce the oncological impacts and consequences of the prolonged outbreak.